Analisis Kinerja Badan Amil Zakat Nasional Kabupaten Siak dalam Mengentaskan Kemiskinan - Hafzan; Saiful Anwar; Mohamad Torik Langlang Buana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
According to BPS data, the poor population in Siak district in 2022 will be 25.71 thousand people or 5.07%. An important factor that can influence the level of poverty is income. A solution from an Islamic perspective to the problem of poverty is optimizing zakat. According to Law Number 23 of 2011 concerning Zakat, it is stated that zakat is to realize community welfare and overcome poverty. One of the institutions formed by the government to manage and distribute zakat, infaq and alms is the National Zakat Amil Agency (BAZNAS). The benchmark for the success of alleviating poverty through optimizing zakat is the performance of BAZNAS. This research analyzes the performance of the Siak Regency National Zakat Amil Agency in its efforts to eradicate poverty. This research has two approaches, namely qualitative and quantitative or mixed method. Data sources used in this research include primary data, secondary data, documents and archives and literature studies. Using interview, observation and questionnaire methods, the performance of BAZNAS Siak Regency can be known through the National Zakat Index 2.0 approach. The components of this index are macro dimensions and micro dimensions. The macro dimension reflects the role of the government and society in contributing to building zakat institutions and the micro dimension describes institutional governance and the impact of zakat. The research results show that BAZNAS Siak Regency in two macro dimensions and micro dimensions obtained good performance scores. The good performance of zakat institutions will influence the results of zakat collection, distribution and utilization programs. The influence of good performance will have a direct impact on mustahik in efforts to improve their welfare which will ultimately help the government in alleviating poverty. In this research, it was found that the impact of good BAZNAS performance for mustahik was materially an increase in income and asset ownership, spiritually in the form of increased worship and awareness of zakat.